An exploratory study regarding the hypothetical human embryo donation in Peru - Álvarez Díaz, Jorge Alberto (2008)
Objective: To explore patients undergoing complex assisted reproductive technologies’ (ART) opinions on both gamete and embryo donation, as well as the reasons to do it or not. Design: Cross-sectional study of descriptive bioethics, with ethnographic qualitative methodology using a semi-structured interview, applying speech analysis to the resulting written transcript. Setting: Private medical institution, in Lima, Peru. Participants: Twenty women and 12 men who had had at least one complex ART. Interventions: Semi-structured interview, applying speech analysis to the resulting written transcript. Main outcome measures: Opinion on both gamete and embryo donation. Results: Regarding embryo donation, 11 men would donate their embryos for infertility treatment, 6 for research purposes, and only one rejected both possibilities. On the other hand, all 20 women would donate embryos for infertility treatment and only 8 for research purposes. Participants who accepted gamete donations did not necessarily think they would donate their own gametes. Conclusions: Results suggest gamete donation is more commented and generally accepted; embryo donation, either to donate or to accept donation, is a more conflicting and less discussed subject. Cryopreservation is a complex subject, commented but also conflicting, whose acceptance or not as well as the probable cryopreserved embryos destiny depend on participants beliefs on life origin, personal ethics, etc. Hypothesis resulting from this study to be verified in future quantitative researches is that embryo donation could take place mainly for infertility treatment and exceptionally for research.